Folatos em brócolis convencional e orgânico e perdas no processo de cocção em água Folates in conventional and organic broccoli and losses during cooking - Juliana Azevedo Lima-Pallone; Rodrigo Ramos Catharino; Helena Teixeira Godoy (Química Nova, 2008)
Broccoli is a vegetable consumed in many countries and a possible source of folates, which are water-soluble vitamins active during DNA synthesis. The folates found in the samples analyzed were 5-methyltetrahydrofolate and 5-formyltetrahydrofolate. The vitamin content varied between 413.7 and 742.2 µg/100 g for 5-methyltetrahydrofolate and from 4.8 to 12.8 µg/100 g for 5-formyltetrahydrofolate. In organic broccoli the amount of 5-methyltetrahydrofolate was significantly higher than in the same vegetable cultivated by traditional methods, for the commercial samples analyzed. The losses of these folates after cooking in water were of approximately 68%, most of it (53%) found in the cooking water.